PPARa gene variants as predicted performance enhancing polymorphisms in professional Italian soccer players - Proia, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
One of the genes of the health-related fitness phenotype is a PPARá coding for peroxisome proliferator activator receptor alpha, a central regulator of expression of genes involved in fatty acid metabolism. Several polymorphic sites have been identifyed whitin the PPARá gene; most of them are very uncommon or where functionally silent. METHODS: Sixty professional soccer players and thirty sedentary volunteers were enrolled in the study. Samples of venous blood were obtained at rest in the morning by conventional clinical procedures and allowed to cloted at room temperature for 30 minutes and centrifuges. Serum was collected and total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol and triglycerides were mesured by using a kit in a chinetic enzyme analyzer. An aliquote of anticoagulant-treated blood was used to prepare total RNA from mononuclear cells. The polymorphic site in PPARá intron 7 was scanned by using PCR-RFLP protocol with Taq I enzyme. RESULTS: We found variations among genotype distribution of PPARá, lipidic profile variation and professional soccer players versus sedentary volunteers. To enphatyzed this correlation, we also investigated mRNA levels of PPARá in mononucleate cells. DISCUSSION: The aim of this study was analyzed the role of polymorphism of PPARá gene in performance enhancing in italian soccer players, compare with the results obtained by Maciejewska et al 2011 in polish rowers. Our results evidenced a variation of genotype distribution of PPARá in accordance with previously studies showing that intron 7 G allele as well as GG genotype, are associated with endurance performance (Ahmetov et al, 2006; Eynon et al, 2009). However, our study shows that PPARá genotype distribution change among analyzed population with varying genetic background. So PPARá G allele may be considered an endurance relates allele. We can explain this one because PPARá is an important factor that regulate the balance between fatty acid and glucose metabolism. Moreover, we analyzed the correlation between PPARá mRNA expression and athletes lipid profile (Proia et al., 2012; Horowitz et al., 2000).